Composite steel beams using precast concrete hollow core floor slabs - Lam, Dennis (1998)
The main aim of this thesis is to develop an insight into the behaviour of composite floors that utilise steel beams acting in combination with precast concrete hollow core floor slabs and to produce design recommendations for use by industry for this type of construction.